Aplicação de indicadores de sustentabilidade na avaliação do sistema de gestão de resíduos sólidos urbanos do município de Cotiporã-RS - Turcatel, Thais (My University, 2019)
The present work presents an evaluation of the municipal waste management system of the municipality of Cotiporã-RS, based on sustainability indicators. The evaluation instrument, represented by a matrix of indicators, was conceived from the application of a method of scientific investigation, called systematic review. As a result, a matrix was composed of 38 indicators, distributed over six dimensions: economic, political, technological/operational, environmental, environmental education and social inclusion.T he data necessary for the application of the matrix were obtained from the analysis of municipal plans related to solid waste, the application of a questionnaire and the collection of information from public entities and directly to the field. In a complementary way, the results obtained from the application of the questionnaire, applied to the resident population in the Municipality, were evaluated from statistical tests, which involved the use of the SPSS statistical package, which allowed, in turn, the foundation for the application of the matrix, as well as obtaining other relevant information in relation to solid urban waste management. Finally, the application of the matrix of sustainability indicators in the municipality of Cotiporã allowed us to identify the critical situations in the management of urban solid waste, and this evaluation has the potential to aid in decision making, allowing the targeting and prioritization of actions and measures management of solid urban waste.(sic)
O presente trabalho traz a avaliação do sistema de gestão de resíduos sólidos urbanos do município de Cotiporã-RS, a partir de indicadores de sustentabilidade. O instrumento de avaliação, representado por uma matriz de indicadores, foi idealizado a partir da aplicação de um método de investigação científica, denominado revisão sistemática. Como resultado obteve-se uma matriz composta por 38 indicadores, sendo estes distribuídos ao longo de 6 dimensões: econômica, política, tecnológica/operacional, ambiental, educação ambiental e inclusão social. Os dados necessários à aplicação da matriz foram obtidos a partir da análise de planos municipais vinculados à temática dos resíduos sólidos, à aplicação de questionário e à coleta de informações junto à entes públicos e diretamente a campo. De maneira complementar, os resultados obtidos a partir da aplicação do questionário, aplicado junto à população residente no Município, foram avaliados a partir de testes estatísticos, que envolveram a utilização do pacote estatístico SPSS, que permitiram por sua vez, o embasamento para a aplicação da matriz, bem como a obtenção de outras informações relevantes em relação à gestão de resíduos sólidos urbanos. Finalmente, a aplicação da matriz de indicadores de sustentabilidade no município de Cotiporã permitiu identificar as situações críticas na gestão dos resíduos sólidos urbanos, sendo que tal avaliação possui potencialidade para o auxílio na tomada de decisão, permitindo o direcionamento e priorização de ações e medidas.(sic)
Keywords: Resíduos sólidos; Sustentabilidade